2015
DOI: 10.1186/s13048-015-0132-8
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of tumor marker CA125 and ovarian tumor stem cells: preliminary identification

Abstract: PurposeThe purpose of this study is to identify a prospective association between CA125 and tumorigenic ovarian cancer cells, using the new method of orthotopic transplantation (1).MethodAfter making the surgical ovarian cancer specimen into cell suspension, we separated the tumorigenic cells from the nontumorigenic cancer cells based on cell surface marker (cancer antigen CA125 and lineage markers) expression. We developed a SCID mice model in which the CA125+/ lineage- and CA125-/ lineage- cells were injecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…These results suggest that self-renewing HGSC cells are located predominantly in the CA125-negative subpopulation. A recent report suggests that CA125-positive cells may also have tumour-initiating capacity 26 . However this report has a number of shortcomings which include (a) lack of controls for cell isolation and tumour take, (b) absence of stringent assays for stem activity and (c) supplementation of tumour-bearing mice with exogenous oestrogen creating a hormonal milieu not physiologic in epithelial ovarian cancer patients.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that self-renewing HGSC cells are located predominantly in the CA125-negative subpopulation. A recent report suggests that CA125-positive cells may also have tumour-initiating capacity 26 . However this report has a number of shortcomings which include (a) lack of controls for cell isolation and tumour take, (b) absence of stringent assays for stem activity and (c) supplementation of tumour-bearing mice with exogenous oestrogen creating a hormonal milieu not physiologic in epithelial ovarian cancer patients.…”
Section: Resultsmentioning
confidence: 99%
“…MUC16-expressing cells are identified as the source of CSCs in ovarian cancer. Studies showed that only CA125 + /lineage − cells form tumors but not CA125 ‐ /lineage ‐ cells in mouse orthotopic implantation [126] . In another study, the role of MUC16 in the enrichment of CSC populations and in tumorigenesis, and its metastatic potential in pancreatic cancer were demonstrated [110] .…”
Section: Cscs and Mucinsmentioning
confidence: 99%
“…The readout in these studies was tumor outgrowth in an orthotopic xenograft. This work led to a rapid increase in papers across many tumor types identifying marker sets that prospectively identified the tumorigenic population in human tumors and cell lines using outgrowth in a xenograft as the proof of stemness (Collins et al 2005;Bao et al 2006;Dalerba et al 2007;Ginestier et al 2007;Hermann et al 2007;Li et al 2007;O'Brien et al 2007;Patrawala et al 2007;Prince et al 2007;Ricci-Vitiani et al 2007;Eramoi et al 2008;Curley et al 2009;Li et al 2009a;Piccirillo et al 2009;Stewart et al 2011;Wang et al 2011;Chen et al 2012;Charafe-Jauffret et al 2013;Wu et al 2013;Zhang et al 2015) (Table 2). In sum, these studies demonstrated minority tumorigenic populations in multiple tumor types including breast, colon, pancreas, head and neck, sarcoma, lung, ovary, AML, and CML.…”
Section: Markers and Modelsmentioning
confidence: 96%
“…After the reports of the first solid tumors to apparently be organized in a cancer stem cell hierarchy (Al-Hajj et al 2003;Singh et al 2004), it was demonstrated that the cancer stem cell compartment size and depth of hierarchy depend on tumor type and that self-renewal assays of tumor regrowth in transplants predict for the biology associated with engraftment in animals, which might not faithfully capture the biology of recurrence in situ (Feuring-Buske et al 2003;Quintana et al 2008;Notta et al 2010;Rehe et al 2013). New markers and strategies to prospectively identify stem cells emerged (Collins et al 2005;Bao et al 2006;Dalerba et al 2007;Ginestier et al 2007;Hermann et al 2007;Li et al 2007;O'Brien et al 2007;Patrawala et al 2007;Prince et al 2007;Ricci-Vitiani et al 2007;Eramo et al 2008;Curley et al 2009;Li et al 2009a;Piccirillo et al 2009;Stewart et al 2011;Wang et al 2011;Chen et al 2012;Charafe-Jauffret et al 2013;Wu et al 2013;Zhang et al 2015), and from these, a series of prognostic signatures were derived across tumor types [Table 1 (Gentles et al 2010;Eppert et al 2011;Merlos-Suarez et al 2011;Bartholdy et al 2014)]. This connection to clinical outcome was reassuring that the cancer stem cell model was relevant.…”
Section: Overview Of the Evolution Of The Cancer Stem Cell Modelmentioning
confidence: 96%